2018
DOI: 10.1101/330985
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct Patterns of the Autofluorescence of Body Surface: Potential Novel Diagnostic Biomarkers for Stable Coronary Artery Disease and Myocardial Infarction

Abstract: Searches for new biomarkers of stable coronary artery disease (SCAD) and myocardial infarction (MI) are critical for therapeutic efficacy of the diseases. In this study we tested our hypothesis that distinct patterns of autofluorescence (AF) of skin and fingernails may become novel diagnostic biomarkers for MI and SCAD.Our study has indicated that SCAD and MI have distinct patterns of AF of their body surface: First, the AF intensity of the MI patients is significantly higher than that of the Healthy and Low-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Our recent studies have suggested that characteristic 'Pattern of AF' could be a novel biomarker for non-invasive diagnosis of acute ischemic stroke (2), acute myocardial infarction (24), stable coronary artery disease (24), Parkinson's disease (3) and lung cancer (11). While oxidative stress could be a key factor leading to the increased epidermal green AF of the patients' skin, future studies are necessary to determine if the increased AF may also be caused by other pathological factors such as inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent studies have suggested that characteristic 'Pattern of AF' could be a novel biomarker for non-invasive diagnosis of acute ischemic stroke (2), acute myocardial infarction (24), stable coronary artery disease (24), Parkinson's disease (3) and lung cancer (11). While oxidative stress could be a key factor leading to the increased epidermal green AF of the patients' skin, future studies are necessary to determine if the increased AF may also be caused by other pathological factors such as inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent studies have suggested that characteristic 'Pattern of Autofluorescence (AF)' could be a novel biomarker for non-invasive diagnosis of AIS (3), MI (25), stable coronary artery disease (25), Parkinson's disease (4) and lung cancer (14). In particular, there are marked and characteristic increases in the green AF intensity in the fingernails and certain regions of the skin of the AIS patients (3) and MI patients (25).…”
Section: Introductionmentioning
confidence: 99%
“…Human autofluorescence (AF) has been used for non-invasive diagnosis of such diseases as diabetes (3,8). Our recent studies have suggested that characteristic 'Pattern of Epidermal Green Autofluorescence (AF)' of each disease may be novel biomarkers for non-invasive diagnosis of a number of diseases, including acute ischemic stroke (AIS) (1), myocardial infarction (MI) (14), stable coronary artery disease (14), Parkinson's disease (2) and lung cancer (7). Our study has also shown that the AF intensity in certain regions of skin is highly correlated with a person's risk to develop AIS, suggesting that the AF may also become a biomarker for evaluation of injury levels of vascular system (6).…”
Section: Introductionmentioning
confidence: 99%